Using a contingent valuation approach for improved solid waste management facility: evidence from Kuala Lumpur, Malaysia - Afroz, Rafia; Masud, Muhammad Mehdi (ELSEVIER, 2011)
This study employed contingent valuation method to estimate the willingness to pay (WTP) of the households to improve the waste collection system in Kuala Lumpur, Malaysia. The objective of this study is to evaluate how household WTP changes when recycling and waste separation at source is made mandatory. The methodology consisted of asking people directly about their WTP for an additional waste collection service charge to cover the costs of a new waste management project. The new waste management project consisted of two versions: version A (recycling and waste separation is mandatory) and version B (recycling and waste separation is not mandatory). The households declined their WTP for version A when they were asked to separate the waste at source although all the facilities would be given to them for waste separation. The result of this study indicates that the households were not conscious about the benefits of recycling and waste separation. Concerted efforts should be taken to raise environmental consciousness of the households through education and more publicity regarding waste separation, reducing and recycling.